2020
DOI: 10.3389/fphys.2020.562895
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on the Effects of 12 Weeks of Aerobic, Resistance, and Combined Exercises Training on the Serum Levels of Nesfatin-1, Irisin-1 and HOMA-IR

Abstract: Background/objective:This study aimed to investigate the impacts of a 12-week training of the aerobic exercise (AE), resistance exercise (RE), and combined exercise (CE) on the serum levels of nesfatin-1, irisin-1 and some other metabolic and anthropometric indices in overweight women with metabolic syndrome. Methods: Sixty overweight women with metabolic syndrome were assigned equally into four groups: aerobic exercise (AE, n = 15), resistance exercise (RE, n = 15), combined exercise (CE, n = 15), and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 58 publications
(83 reference statements)
2
73
0
Order By: Relevance
“…The results of the meta-analysis indicated a moderate and non-significant effect of resistance training programs in increasing circulating irisin, as indicated by the overall effect size in Figure 2 (d = 0.58, 95% CI: −0.25 to 1.40, p = 0.17). [35][36][37][38][39]41,42]. Squares represent the standardized mean difference for each study and diamond represents the overall estimated effect across the studies.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the meta-analysis indicated a moderate and non-significant effect of resistance training programs in increasing circulating irisin, as indicated by the overall effect size in Figure 2 (d = 0.58, 95% CI: −0.25 to 1.40, p = 0.17). [35][36][37][38][39]41,42]. Squares represent the standardized mean difference for each study and diamond represents the overall estimated effect across the studies.…”
Section: Meta-analysismentioning
confidence: 99%
“…Therefore, subgroup analysis showed significant differences across groups according to (a) age (χ 2 = 15.66, p < 0.001) with a high and significant increase in circulating irisin in the older adults group (d = 2.01, 95% CI: 1.31 to 2.70, p < 0.001) and a non-significant increase in adults group (d = 0.04, 95% CI: −0.64 to 0.73, p = 0.36) ( Figure 3); (b) change in % body fat (χ 2 = 12.93, p < 0.001) with non-significant changes in circulating irisin when the % body fat did not change during the intervention period (d = −0.42, 95% CI: −1.13 to 0.30, p = 0.25) and a high and significant increment when the % body fat decreased throughout the intervention period (d = 1.42, 95% CI: 0.72 to 2.12, p < 0.001) ( Figure 4); (c) intervention duration (χ 2 = 17.52, p < 0.001), with a high and significant increase in circulating irisin when the duration of the intervention was less or equal to 12 weeks (d = 1.13, 95% CI: 0.35 to 1.91, p = 0.005) and moderate and significant decreases when it lasted more than 4 months (d = −0.68, 95% CI: −1.01 to −0.35, p < 0.001) ( Figure 5); and (d) supervised sessions (χ 2 = 8.35, p = 0.004) with a moderate and significant decrease in circulating irisin when less than 80% of the sessions were supervised (d = −0.73, 95% CI: −1.21 to −0.25, p = 0.004) and high but non-significant increases when more than 80% of the sessions were supervised (d = 0.82, 95% CI: −0.11 to 1.76, p = 0.09) ( Figure 6). [35][36][37][38][39]41,42]. Squares represent the standardized mean difference for each study and diamonds represent the subgroup estimated effect across the studies.…”
Section: Effect Of Moderator Variablesmentioning
confidence: 99%
“…Exercise prescriptions based on endurance, aerobic interval, and/or muscular-strengthening exercises have been used for improving physical and metabolic parameters in MetS [ 20 , 21 ] as well as prevention [ 65 ]. This study showed the effect of a combined exercise modality consisting of endurance and resistance training regimens on the circulating biomarker levels of mitochondrial stress along with improved physical fitness and alleviated cardio-metabolic risks.…”
Section: Discussionmentioning
confidence: 99%
“…To maximize the physical and metabolic benefits from exercise training, we adopted a combined endurance and strength exercise regimen. We used a 12-week intervention program which enhanced physical fitness, as well as metabolic improvements were shown [ 20 , 21 ]. Participants performed a 50 min exercise routine that combined step aerobics using height-adjustable platforms and progressive strength training using various body weights and elastic bands (Thera-Band, Hygenic Co., Akron, OH, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Similar divergent results have been reported for the correlation between circulating irisin and insulin resistance [ 19 ]. Although most studies agree that circulating irisin is positively correlated with insulin resistance, no consensus opinion exists regarding the association of irisin and metabolic syndrome [ 15 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Those who observed that a reduction in irisin is associated with an increased risk of hyperglycemia or metabolic syndrome suggest the protective role of irisin against insulin resistance, similar to the relationship observed with adiponectin in metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%